A STUDY OF THE TEACHERS’ ROLES IN THE IMPLEMENTATION OF SCIENTIFIC APPROACH IN TEACHING ENGLISH AT SMP NEGERI 1 SINGARAJA - Ayustina, K.P.P.; Batan, I.G.; Mahayanti, N.W.S. (Universitas Pendidikan Ganesha, 2018)
The implementation of Curriculum 2013 indicated that there is a switch of the teachers’ role in the process of teaching and learning from resource becoming facilitator. This study aimed to find out the roles that the teachers play in the classrooms when teaching English at SMP Negeri 1 Singaraja and to know responses of the students toward it. It followed qualitative interactive descriptive model, approach, and design which was adopting the framework of Maxwell (2012). It involved 3 teachers and 174 students. The required data for this study were collected through observation and distributing questionnaire. Since the data were analyzed descriptively, it was adopted the framework developed by Miles and Huberman (1994). The results of data analysis show that there are five roles the teachers played in the classroom when teaching English at SMP Negeri 1 Singaraja such as prompter or motivator, facilitator, controller, organizer, and assessor and the responses of the students toward it mostly dominated by positive attitude. In short, most of the roles that the teachers played support the student-centered learning. It is the result of the classroom focused activities developing on giving exercises, completing task, and doing practice of language used. Keywords: assessor, controller, facilitator, organizer, prompter, scientific approach